2014
DOI: 10.1111/ajco.12091
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum C-reactive protein, carcinoembryonic antigen and N2 disease are poor prognostic indicators in non-small cell lung cancer

Abstract: High levels of serum CRP and CEA, and N2 disease are independent prognostic indicators for the survival of patients with stage III-IV NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…Among them, TNF-α is likely to play a central role in tumorigenesis, as it has been reported that mice deficient with TNF-α is protected from the cancer development [44,45]. Furthermore, CRP is considered to play a major role in cancer development [28,29]. Our study demonstrated that Ang II could directly induce inflammatory cytokines TNF-α and CRP productions in HCC cell lines.…”
Section: Discussionsupporting
confidence: 55%
“…Among them, TNF-α is likely to play a central role in tumorigenesis, as it has been reported that mice deficient with TNF-α is protected from the cancer development [44,45]. Furthermore, CRP is considered to play a major role in cancer development [28,29]. Our study demonstrated that Ang II could directly induce inflammatory cytokines TNF-α and CRP productions in HCC cell lines.…”
Section: Discussionsupporting
confidence: 55%
“…This might be a result of different inclusion criteria and the addition of PLR and other factors in the multivariate survival analyses. Some other recent studies have also demonstrated that elevated CRP is independently associated with poor survival …”
Section: Discussionmentioning
confidence: 86%
“…The tumor group of our study population comprised patients with lung cancer as the largest subgroup of patients. Interestingly, several studies have recently indicated the value of CEA in the diagnosis and prognosis of lung cancer with PEs, among other biomarkers . Indeed, high serum CRP and CEA levels were identified as independent prognostic indicators for the survival of patients with stage III–IV non‐small cell lung cancer (NSCLC) .…”
Section: Discussionmentioning
confidence: 99%